Trade Union Studies - cartoon, 1975 (London, 1975)
1975 1974-79 "Trade Union Studies - cartoon, 1975" [BW0177], 1975, Trades Union Congress The Trade Union Studies project comprised television programmes, postal courses and publications produced by the BBC, TUC Education Service and the Workers' Educational Association. There were three successive TV series, each with a book, spanning three years from Autumn 1975. The course books included several cartoons by Larry [Terence Parkes].